Cholesterol lowering effects of mono-lactose-appended β-cyclodextrin in Niemann–Pick type C disease-like HepG2 cells - Motoyama, Keiichi; Hirai, Yumi; Nishiyama, Rena; Maeda, Yuki; Higashi, Taishi; Ishitsuka, Yoichi; Kondo, Yuki; Irie, Tetsumi; Era, Takumi; Arima, Hidetoshi (Beilstein Journal of Organic Chemistry, 2015)
The Niemann–Pick type C disease (NPC) is one of inherited lysosomal storage disorders, emerges the accumulation of unesterified cholesterol in endolysosomes. Currently, 2-hydroxypropyl-β-cyclodextrin (HP-β-CyD) has been applied for the treatment of NPC. HP-β-CyD improved hepatosplenomegaly in NPC patients, however, a high dose of HP-β-CyD was necessary. Therefore, the decrease in dose by actively targeted-β-CyD to hepatocytes is expected. In the present study, to deliver β-CyD selectively to hepatocytes, we newly fabricated mono-lactose-appended β-CyD (Lac-β-CyD) and evaluated its cholesterol lowering effects in NPC-like HepG2 cells, cholesterol accumulated HepG2 cells induced by treatment with U18666A. Lac-β-CyD (degree of substitution of lactose (DSL) 1) significantly decreased the intracellular cholesterol content in a concentration-dependent manner. TRITC-Lac-β-CyD was associated with NPC-like HepG2 cells higher than TRITC-β-CyD. In addition, TRITC-Lac-β-CyD was partially localized with endolysosomes after endocytosis. Thus, Lac-β-CyD entered NPC-like HepG2 cells via asialoglycoprotein receptor (ASGPR)-mediated endocytosis and decreased the accumulation of intracellular cholesterol in NPC-like HepG2 cells. These results suggest that Lac-β-CyD may have the potential as a drug for the treatment of hepatosplenomegaly in NPC disease.
Keywords: asialoglycoprotein receptor; cholesterol; cyclodextrin; lactose; Niemann–Pick disease type C

(untitled) - Carstea, E. D.; Morris, J. A.; Coleman, K. G.; Loftus, S. K.; Zhang, D.; Cummings, C.; Gu, J.; Rosenfeld, M. A.; Pavan, W. J.; Krizman, D. B.; Nagle, J.; Polymeropoulos, M. H.; et al. (Science, 1997)

(untitled) - Naureckiene, S.; Sleat, D. E.; Lackland, H.; Fensom, A.; Vanier, M. T.; Wattiaux, R.; Jadot, M.; Lobel, P. (Science, 2000)

(untitled) - Vanier, M. T. (Orphanet J. Rare Dis., 2010)

(untitled) - Matsuo, M.; Togawa, M.; Hirabaru, K.; Mochinaga, S.; Narita, A.; Adachi, M.; Egashira, M.; Irie, T.; Ohno, K. (Mol. Genet. Metab., 2013)

(untitled) - Szente, L.; Szejtli, J. (Adv. Drug Delivery Rev., 1999)

(untitled) - Uekama, K.; Otagiri, M. (Crit. Rev. Ther. Drug Carrier Syst., 1987)

(untitled) - Davidson, C. D.; Ali, N. F.; Micsenyi, M. C.; Stephney, G.; Renault, S.; Dobrenis, K.; Ory, D. S.; Vanier, M. T.; Walkley, S. U. (PLoS One, 2009)

(untitled) - Liu, B.; Turley, S. D.; Burns, D. K.; Miller, A. M.; Repa, J. J.; Dietschy, J. M. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Porter, F. D.; Scherrer, D. E.; Lanier, M. H.; Langmade, S. J.; Molugu, V.; Gale, S. E.; Olzeski, D.; Sidhu, R.; Dietzen, D. J.; Fu, R.; Wassif, C. A.; Yanjanin, N. M.; et al. (Sci. Transl. Med., 2010)

(untitled) - Soga, M.; Ishitsuka, Y.; Hamasaki, M.; Yoneda, K.; Furuya, H.; Matsuo, M.; Ihn, H.; Fusaki, N.; Nakamura, K.; Nakagata, N.; Endo, F.; Irie, T.; et al. (Stem Cells, 2015)

(untitled) - D'Souza, A. A.; Devarajan, P. V. (J. Controlled Release, 2015)

(untitled) - Okamatsu, A.; Motoyama, K.; Onodera, R.; Higashi, T.; Koshigoe, T.; Shimada, Y.; Hattori, K.; Takeuchi, T.; Arima, H. (Bioconjugate Chem., 2013)

(untitled) - Okamatsu, A.; Motoyama, K.; Onodera, R.; Higashi, T.; Koshigoe, T.; Shimada, Y.; Hattori, K.; Takeuchi, T.; Arima, H. (Biomacromolecules, 2013)

(untitled) - Darblade, B.; Caillaud, D.; Poirot, M.; Fouque, M.-J.; Thiers, J.-C.; Rami, J.; Bayard, F.; Arnal, J.-F. (Cardiovasc. Res., 2001)

(untitled) - Parpal, S.; Karlsson, M.; Thorn, H.; Strålfors, P. (J. Biol. Chem., 2001)

(untitled) - Sugimoto, Y.; Ninomiya, H.; Ohsaki, Y.; Higaki, K.; Davies, J. P.; Ioannou, Y. A.; Ohno, K. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - van Gelder, C. M.; Vollebregt, A. A. M.; Plug, I.; van der Ploeg, A. T.; Reuser, A. J. J. (Expert Opin. Pharmacother., 2012)

(untitled) - Vance, J. E.; Karten, B. (J. Lipid Res., 2014)

(untitled) - Rosenbaum, A. I.; Maxfield, F. R. (J. Neurochem., 2011)

(untitled) - Rosenbaum, A. I.; Zhang, G.; Warren, J. D.; Maxfield, F. R. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Elrick, M. J.; Yu, T.; Chung, C.; Lieberman, A. P. (Hum. Mol. Genet., 2012)

(untitled) - Ishibashi, S.; Yamazaki, T.; Okamoto, K. (J. Clin. Neurosci., 2009)

(untitled) - Ordonez, M. P.; Roberts, E. A.; Kidwell, C. U.; Yuan, S. H.; Plaisted, W. C.; Goldstein, L. S. B. (Hum. Mol. Genet., 2012)

(untitled) - Sarkar, S.; Carroll, B.; Buganim, Y.; Maetzel, D.; Ng, A. H. M.; Cassady, J. P.; Cohen, M. A.; Chakraborty, S.; Wang, H.; Spooner, E.; Ploegh, H.; Gsponer, J.; et al. (Cell Rep., 2013)

(untitled) - Lieberman, A. P.; Puertollano, R.; Raben, N.; Slaugenhaupt, S.; Walkley, S. U.; Ballabio, A. (Autophagy, 2012)

(untitled) - Nixon, R. A. (Nat. Med., 2013)

(untitled) - Song, W.; Wang, F.; Lotfi, P.; Sardiello, M.; Segatori, L. (J. Biol. Chem., 2014)

(untitled) - Tamura, A.; Yui, N. (J. Biol. Chem., 2015)

(untitled) - Stokmaier, D.; Khorev, O.; Cutting, B.; Born, R.; Ricklin, D.; Ernst, T. O. G.; Böni, F.; Schwingruber, K.; Gentner, M.; Wittwer, M.; Spreafico, M.; Vedani, A.; et al. (Bioorg. Med. Chem., 2009)

(untitled) - Onodera, R.; Motoyama, K.; Arima, H. (J. Inclusion Phenom. Macrocyclic Chem., 2011)